2001
DOI: 10.1207/s15328015tlm1304_03
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Patients' Perceptions About Their Own Health Care

Abstract: As a consequence of their participation, the SPs indicated a change in attitudes about their personal health care. They perceived improved understanding and ability to communicate and comfort with their own health care. Participation in SP programs seems to influence SPs by improving perceptions about their own health care interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
1
18
1
2
Order By: Relevance
“…A positive aspect of the simulated patient role is that the simulators become more knowledgeable about their own health (Wallach et al, 2001).…”
Section: Advantages and Disadvantages Of Simulated Patientsmentioning
confidence: 99%
“…A positive aspect of the simulated patient role is that the simulators become more knowledgeable about their own health (Wallach et al, 2001).…”
Section: Advantages and Disadvantages Of Simulated Patientsmentioning
confidence: 99%
“…SPs, experienced in medical communication either with OSCEs or teaching for medical students were invited to reflect on the relationship with their usual HCP. The authors concluded that SPs felt more comfortable and communicated more effectively with their own HCP [7]. SPs reported a better understanding of medical history taking and physical examination [7] and perceived their ability to judge the quality of a health care interaction as improved [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Literature of studies on side effects reveals two main areas: influences of simulating on personal health and influences on the perception of and contact with their own health care provider (HCP) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations